Association of preoperative systemic inflammation with postoperative conduction block in TAVI patients - Shi, Ying-Lu; Di, Dong-Sheng; Zhang, Cheng-Xin; Gong, Wen-Hui; Ge, Sheng-Lin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundConduction block (CB) is a frequent complication following transcatheter aortic valve implantation (TAVI). Systemic inflammation may play a role in its development, but evidence is limited.MethodsThis prospective study included 155 patients who underwent TAVI. Preoperative systemic inflammation markers—including systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR)—were analyzed in relation to postoperative conduction block and cardiac function using logistic and linear regression models, as well as restricted cubic spline analysis.ResultsPostoperative conduction block occurred in 35.5% of patients. Higher preoperative SII (OR = 1.0009; P = 0.0289), NLR (OR = 1.1630; P = 0.0253), and PLR (OR = 1.0079; P = 0.0065) were significantly associated with increased CB risk, while higher LMR was protective (OR = 0.7435; P = 0.0194). LMR was also independently associated with reduced ejection fraction and increased left ventricular volume. Gender subgroup analysis showed stronger associations in females.ConclusionPreoperative systemic inflammation is independently associated with conduction block and cardiac function outcomes after TAVI. Inflammation-based biomarkers may serve as useful tools for risk stratification and perioperative planning.